2013
DOI: 10.1093/ntr/ntt087
|View full text |Cite
|
Sign up to set email alerts
|

Time to First Cigarette Predicts Cessation Outcomes in Adolescent Smokers

Abstract: introduction: This study examined the relationship between the time to the first cigarette (TTFC) of the morning with quit status among adolescent smokers at the completion of a school-based smoking cessation program. Among those who did not quit, the relationship of TTFC with changes in cigarettes/day (CPD) was also examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 35 publications
(55 reference statements)
0
17
0
Order By: Relevance
“…In a large sample European Americans seeking treatment for smoking cessation (the U. Wisconsin Transdisciplinary Tobacco Use Research Center smoking cessation trials (McCarthy et al, ; Piper et al, ; Piper et al, )), a significant association was found between FMO3 genotype and scores reported for the Fagerström Test of Nicotine Dependence (FTND), the most widely used instrument for measuring nicotine dependence. Among the questionnaire items from the FTND, ‘time to first cigarette’ and ‘cigarettes per day’ are the two strongest predictors of smoking cessation (Baker et al, ; Mercincavage, Branstetter, Muscat, & Horn, ; Rohsenow, Martin, Tidey, Monti, & Colby, ). Importantly, the association between FMO3 genotype and FTND score was driven entirely by the time to first cigarette, and unlike CYP2A6 , FMO3 genotype was not significantly associated with overall cigarette consumption among dependent smokers.…”
Section: Discussionmentioning
confidence: 99%
“…In a large sample European Americans seeking treatment for smoking cessation (the U. Wisconsin Transdisciplinary Tobacco Use Research Center smoking cessation trials (McCarthy et al, ; Piper et al, ; Piper et al, )), a significant association was found between FMO3 genotype and scores reported for the Fagerström Test of Nicotine Dependence (FTND), the most widely used instrument for measuring nicotine dependence. Among the questionnaire items from the FTND, ‘time to first cigarette’ and ‘cigarettes per day’ are the two strongest predictors of smoking cessation (Baker et al, ; Mercincavage, Branstetter, Muscat, & Horn, ; Rohsenow, Martin, Tidey, Monti, & Colby, ). Importantly, the association between FMO3 genotype and FTND score was driven entirely by the time to first cigarette, and unlike CYP2A6 , FMO3 genotype was not significantly associated with overall cigarette consumption among dependent smokers.…”
Section: Discussionmentioning
confidence: 99%
“…1 = within 5 minutes; 2 = 6-30 minutes; 3 = from more than 30 minutes to 1 hour; and 4 = more than 1 hour) that has been adopted by later nicotine dependence questionnaires, including the Fagerström Test for Nicotine Dependence (FTND; [11]). Since Kozlowski and colleagues' initial work on TTFC, a number of studies have confirmed that TTFC may be the single best predictor of nicotine dependence; an earlier time to first cigarette is closely associated with poor smoking outcomes such as increased levels of tobacco exposure biomarkers, increased tolerance and decreased likelihood of quitting during and an inability to maintain abstinence following a quit attempt [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…(ITT) sample, participants were considered to have experienced failure to quit if they reported continuing smoking or were not available for followup at 3-months post baseline. Conservatively, analysis assumed that unavailable participants continued to smoke, accounting for 27% of the treatment failure sample 34,36 . The study uniquely applied 'treatment failure', unlike the majority of tobacco cessation studies that commonly focus on quit rates 9,[37][38][39] .…”
Section: Data Sourcesmentioning
confidence: 99%
“…pack-years). TTFC has been shown to be highly related to: nicotine dependence, exposure to nicotine and carcinogens in both adolescent daily and non-daily smokers, and cessation outcomes among adolescents 36,[52][53][54] (Table 1).…”
Section: Predictor Variablesmentioning
confidence: 99%